Impact of New Complete Dentures on Dietary Intervention and Masticatory Performance in Geriatric Patients - Muhammad Afzal Khan, Nasir Ali, Palwasha Rauf, Shafqat Hussain, Sajid Ali, Hamad Ishtiaq (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To evaluate the impact of new complete dentures on masticatory efficiency and dietary quality among geriatric patients and compare outcomes with national and international literature. Methodology: Thirty edentulous geriatric patients (≥60 years) received new complete dentures. Masticatory efficiency was measured using a color-change chewing test, whereas dietary quality was evaluated using a validated diet score. Assessments occurred at baseline and 8 weeks post-insertion. Paired t-tests analyzed changes, and Pearson correlation assessed the relationship between functional improvement and diet. Results: Masticatory efficiency increased significantly from 49.2 ± 3.1 to 72.4 ± 3.3 (p < 0.001). Diet quality improved from 33.4 ± 2.5 to 48.2 ± 3.1 (p < 0.001). A moderate positive correlation (r = 0.62) was found between increases in chewing efficiency and dietary score. Participants reported enhanced ability to chew firm foods, increased confidence, and reduced avoidance of nutritious food items. Conclusion: Complete dentures significantly restore chewing function and moderately enhance diet quality. However, optimal nutritional improvement requires integration of prosthodontic treatment with dietary counseling and structured follow-up support. Keywords: Edentulous, complete denture, geriatric patients, masticatory performance, dietary intervention.